Lanskap Linguistik Maya pada Katalog Distro BetawiBoys dan Sikap Bahasa - Rafif Aufa Nanda; Frans Asisi Datang (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
In accordance with technological development, linguistic landscape is not only limited to physical landscape, but also virtual linguistic landscape on internet media, such as social media. Language usage choice is influenced by the language attitude towards a language. This research seeks to observe the language usage and attitude on an online catalogue of Distro BetawiBoys, a Batavian culture themed fashion store. There are 30 pictures which contain the use of Batavian, Indonesian, and English. The data are analysed by using a mixed method approach. The result shows that the use of Batavian is predominant that other languages that are often deemed to be more prestigious. This shows a positive language attitude towards regional language. Moreover, these findings shows an unusual result where most findings in Indonesian linguistic landscapes show the dominance of more prestigious languages.